BATIK TRAINING ON NURSING HOUSE ‘WANITA UTAMA’ SURAKARTA - Asri Laksmi Riani; Sarah Rum Handayani; Rahmawati Rahmawati (Jurnal Ilmiah Teknik Industri, 2011)
The purpose of this study is to be able to guide and direct the prostitutes (WTS) in Surakarta and it’s surrounding environment on the nursing house "Wanita Utama" Surakarta who want to change profession to have the insight and skills of entrepreneurial attitudes and skills of batik. Debriefing is done by providing counseling and training-related such as entrepreneurship training, providing knowledge about batik and batik business, as well as training with the kinds of batik: handmade writing batik, printed batik and combination batik. The implication of this activity is the opening insight into the participants on the batik activities and can be seen from the enthusiasm of participants to propose on batik courses in other kinds such as batik dyeing. Most of the participants wanted a follow-up of these training efforts as well as assistance and for giving a confidence to be responsible for their future.